The effect of Urtica dioica drop on postpartum hemorrhage: A triple-blind randomized clinical trial - Fatemeh Bakhshalizadeh; Padideh Janati Ataei; Faraz Mojab; Maliheh Nasiri; Zohreh Mahmoodi (Mashhad University of Medical Sciences, 2022)
Introduction: Postpartum hemorrhage is the most leading cause of maternal mortality worldwide; prevention of it can be effective in reducing mortality and complications. Studies have shown the contractile and anti-inflammatory properties of Urtica dioica and its effect on reducing menstrual bleeding, so the present study was performed aimed to determine the effect of Urtica dioica drops on postpartum hemorrhage. Methods: This triple-blind randomized clinical trial study was conducted in 2019 on 100 women referred to Kamali Hospital in Karaj (Iran) for vaginal delivery in two groups of intervention and control. The intervention group received 10 drops of Urtica dioica and the control group received 10 placebo drops after delivery. Bleeding was measured using PBLAC chart up to 24 hours after delivery. Hemoglobin and hematocrit levels were measured at arrival and 6 hours postpartum. Data were analyzed using SPSS software (version 20) and independent t-test, Mann-Whitney, Fisher, Chi-square and repeated measures ANOVA. P<0.05 was considered statistically significant. Results: There was no statistically significant difference between the two groups in terms of demographic and obstetric variables (p>0.05). The mean of bleeding in the first 24 hours after delivery was 55.94±11.55 ml for the intervention group and 71.48±12.45 ml for the control group, which was significantly different (p=0.001). Also, the mean decrease of hemoglobin (p = 0.006) and hematocrit (p = 0.001) level was significantly lower in the Urtica dioica group than the control group. Conclusion: Urtica dioica drop have a significant effect on reducing bleeding and reducing hemoglobin and hematocrit after childbirth and is helpful in reducing postpartum hemorrhage.